EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK WDEP UNTUK MENINGKATKAN PEMAHAMAN DIRI SISWA DI SMPN 3 BANDAR PULAU - Dewi Purnama Sari; Alfin Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of group guidance services using the WDEP technique in improving students' self-understanding. This study used a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The study sample consisted of 30 students, consisting of 15 in the experimental group and 15 in the control group, selected using purposive sampling. Data collection was conducted using a self-understanding questionnaire with a Likert scale. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using independent sample t-tests using SPSS. The results showed that the average self-understanding score in the experimental group increased from 62.20 in the pretest to 84.27 in the posttest, while in the control group it increased from 63.13 to 69.13. The results of the hypothesis test showed a significance value of 0.000 <0.05, so Ha was accepted and Ho was rejected. Thus, group guidance services using the WDEP technique were effective in improving students' self-understanding.